2017
DOI: 10.21315/mjms2017.24.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Lavage of the Peritoneal Cavity with Lidocaine, Bupivacaine and Normal Saline to Reduce the Formation of Abdominal Adhesion Bands in Rats

Abstract: Background: Intra-abdominal adhesions are fibrous bands that develop after abdominal surgery or inflammation and cause mortality and morbidity following surgeries. This study aimed to assess the effects of bupivacaine, saline and two doses of lidocaine, after peritoneal lavage and to compare their effects in reducing abdominal adhesions in rat.Methods: In a blinded, randomised, placebo-controlled clinical trial, 50 female rats were anaesthetised and the parietal peritoneum was scratched to induce punctate blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In the literature, normal saline had already been reported to reduce adhesion formation in an experimental adhesion model [16]. On the other hand, several studies reported that there is no influence of saline on PPA prevention [18,19]. Normal saline is also commonly used in surgical practice for intra-operative lavage to remove contaminants and debris in order to prevent PPA.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, normal saline had already been reported to reduce adhesion formation in an experimental adhesion model [16]. On the other hand, several studies reported that there is no influence of saline on PPA prevention [18,19]. Normal saline is also commonly used in surgical practice for intra-operative lavage to remove contaminants and debris in order to prevent PPA.…”
Section: Discussionmentioning
confidence: 99%
“…The ethanol extract of the plant has shown antibacterial effects against a number of grampositive (Listeria monocytogens, Staphylococcus aureus, and Staphylococcus epidermidis) strains [11]. Several studies have reported that Persica mouthwash has anti-plaque, anti-bleeding, anti-ulcer [12], analgesic and antimicrobial effects with no side effects from chemical mouthwashes [13]. Octacosanol, 1triacantanol, β-sitosterol, and β-sitosterol-3-O-β-Dglucopyranoside were isolated from the stem of the plant through phytochemical investigations [14].…”
Section: Introductionmentioning
confidence: 99%
“…Frequent exposure to environments contaminated with these gases leads to cell damage, increased cell proliferation, hyperplasia, and ultimately tumor growth 21 . Studies have shown that inhaling more than 10 ppm of nitric oxide and more than 15 ppm of halothane and enluran can impair the functioning of the nervous system 22 , 23 .…”
Section: Introductionmentioning
confidence: 99%